The Effect Recombinant Growth Hormone (rGH) Base on Different Age and Duration of Immersion on Growth and Survival Rate of Bonylip Barb Larvae (Osteochilus vittatus) - Nova Handayani; Nuraini Nuraini; Netti Aryani (Jurnal Akuakultur SEBATIN, 2023)
This research was conducted on September - October 2021, at Fish Hatchery and Breeding Laboratory of Fishery and Marine Faculty of Riau University. The research aim is to determine the effect of Recombinant Growth Hormone (rGH) with optimal doses based on different age and immersion duration on growth and survival rate of Bonylip Barb larvae. The method used was Completely Randomized Design Factorial with 2 factors. The first factor was larvae age with 3 levels, namely 5 days (U5), 7 days (U7) and 9 days (U9). The second factor is . the immersion time with 4 levels, namely 0 minutes (P0), 10 minutes (P10), 20 minutes (P20) and 30 minutes (P30). Larvae was kept for 40 days in an aquarium with a density of 2 fish/L. From the result of research showed that recombinant growth hormone (rGH) with different larvae age and immersion time affected the growth of Bonylip Barb absolute weight and length, specific growth rate, and also survival rate of larvae. The treatment of 9 days of larvae age (U5P30) showed the highest growth, namely absolute weight and 60 minutes immersion time showed the highest growth, namely absolute weight 1,08 g, absolute length 4,48 cm, specific growth rate of 16,10/day, and survival rate 94,43%. The parameter of water quality during the research was 26,5-27,8°C, pH 5,0-6,5, and dissolved oxygen 4,0-5,3 mg/L.